2017
DOI: 10.1177/0269094217727236
|View full text |Cite
|
Sign up to set email alerts
|

Connected growth: Developing a framework to drive inclusive growth across a city-region

Abstract: This ‘in perspective’ piece addresses the (re-)positioning of civil society within new structures of city-region governance within Greater Manchester. This follows on from the processes of devolution, which have given the Greater Manchester City-Region a number of new powers. UK devolution, to date, has been largely focused upon engendering agglomerated economic growth at the city-region scale. Within Greater Manchester City-Region, devolution for economic development has sat alongside the devolution of health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…In addressing this and offering new knowledge, future research in this rural vein can contribute to the emerging literature on inclusive growth via city-region-building (Beel, Jones, Jones, & Escadale, 2017;Bevan Foundation and Joseph Rowntree Foundation, 2017;Lee, 2019;Vickers, Spear, Brennan, & Syrett, 2017). This is seeking out a new economic model, and for the likes of the Royal Society of Arts (RSA) (2016, 2017), with regards to social and economic policy, reducing inequality and deprivation can itself drive growth.…”
Section: Discussionmentioning
confidence: 99%
“…In addressing this and offering new knowledge, future research in this rural vein can contribute to the emerging literature on inclusive growth via city-region-building (Beel, Jones, Jones, & Escadale, 2017;Bevan Foundation and Joseph Rowntree Foundation, 2017;Lee, 2019;Vickers, Spear, Brennan, & Syrett, 2017). This is seeking out a new economic model, and for the likes of the Royal Society of Arts (RSA) (2016, 2017), with regards to social and economic policy, reducing inequality and deprivation can itself drive growth.…”
Section: Discussionmentioning
confidence: 99%
“…More critically, Etherington and Jones (2009) have questioned the usefulness of the city-region as an administrative level. They showed that the competitiveness model increases uneven development, and certain levels of inequality can even hinder growth (a conclusion also reached by Beel, Jones, Jones, & Escadale, 2017;andPastor, 2015a, 2015b). In a study of English devolution, Etherington and Jones (2016, p. 386) argue that the current framework of the deals agreed between city-regions and the UK government will only exacerbate the 'deeply historical problem of uneven growth', leaving disadvantaged groups voiceless.…”
Section: The City-region Debate In the Progressive Regionalism Literamentioning
confidence: 80%
“…His study confirms that although effects can sometimes be limited, enhancing public involvement in (re-) forming city-regions could heighten democratic practices and shape the path towards a 'comprehensively progressive' region. Looking at Greater Manchester, Beel et al (2017) made the case for civil society actors to be strongly represented in city-regional governance structures. These stakeholders' expertise and innovative approaches have better chances at filtering down economic development to places and people previously left out.…”
Section: The City-region Debate In the Progressive Regionalism Literamentioning
confidence: 99%
“…Концепция и политика инклюзивного роста/развития ставят главной целью не увеличение валового регионального продукта (т. е. количества произведенных в регионе товаров, услуг и работ), а повышение качества жизни всех групп населения, которое измеряется не только уровнем реально располагаемых доходов, но и возможностями трудоустройства, безопасностью, комфортностью среды проживания, возможностями самовыражения, активностью культурной жизни, удобством инфраструктуры, толерантностью, эмоциональным климатом территории. Кроме того, инклюзивное развитие предполагает сглаживание чрезмерных диспропорций между различными муниципальными образованиями, что отражено в идее связанного роста агломераций и регионов (Beel, Jones, Rees, Escadale, 2017).…”
Section: маркетинг и брендинг территорий: стейкхолдеры решают всеunclassified